Reconfiguring Ruins: Beyond Ruinenlust. Issue 2 (3rd July 2017) - López Galviz, Carlos; Bartolini, Nadia; Pendleton, Mark; Stock, Adam
Abstract : What explains the global proliferation of interest in ruins? Can ruins be understood beyond their common framing as products of European Romanticism? Might a transdisciplinary approach allow us to see ruins differently? These questions underpinned the Arts and Humanities Research Council–funded project Reconfiguring Ruins, which deployed approaches from history, literature, East Asian studies, and geography to reflect on how ruins from different historical contexts are understood by reference to different theoretical frameworks. In recognition of the value of learning from other models of knowledge production, the project also involved a successful collaboration with the Museum of London Archaeology and the artist-led community The NewBridge Project in Newcastle. By bringing these varied sets of knowledges to bear on the project's excavations of specific sites in the United Kingdom, the United States, and Japan, the article argues for an understanding of ruins as thresholds, with ruin sites providing unique insights into the relationship between lived pasts, presents, and futures. It does so by developing three key themes that reflect on the process of working collaboratively across the arts, humanities, and social sciences, including professional archaeology: inter- and transdisciplinarity, the limits of cocreation, and traveling meanings and praxis. Meanings of specific ruins are constructed out of specific languages and cultural resonances and read though different disciplines, but can also be reconfigured through concepts and practices that travel beyond disciplinary, cultural, and linguistic borders. As we show here, the ruin is, and should be, a relational concept that moves beyond the romantic notion of Ruinenlust .